Energy, emissions and economic impact of the new nZEB regulatory framework on residential buildings renovation: Case study in southern Spain. (October 2021) - Cerezo-Narváez, Alberto; Piñero-Vilela, José-María; Rodríguez-Jara, Enrique-Ángel; Otero-Mateo, Manuel; Pastor-Fernández, Andrés; Ballesteros-Pérez, Pablo
Abstract: Spanish residential buildings built in the decade of the housing bubble (2000–2009) had to comply with the Basic Buildings Standard on thermal conditions in buildings. At the end of this period, the Basic Energy Savings Document of the Technical Building Code published in the Royal Decree 314/2006, transposing European Directive 2002/91/EC, entered into force. Recently, this regulatory framework has been updated by the Royal Decree 732/2019, which transposes European Directives 2010/31/EU, 2012/27/EU and 2018/844/EU. A case study is used to analyse the energy, emissions and economic impact of these regulatory changes on an attached house located in all municipalities of Andalusia (South of Spain). The thermal behaviour of this house is compared with the one adapted to the new regulations. The TRNSYS transient system simulation tool is used for the energy study. The house adaptation is carried out by partially modifying the envelope, including a solar-thermal contribution to domestic hot water supply, and photovoltaic energy production to reduce electricity consumption. The results showed that the European objectives are greatly exceeded. Energy savings range from 69% to 127%, carbon dioxide emissions decrease by 65%–118%, and energy bills are reduced from 71% to 125%. Highlights: Recent Spanish regulations on energy efficiency have notably reduced HEAT demands. Renovation of buildings is environmentally and economically advisable in Andalusia. Housing DHW demands can be drastically reduced on installing a domestic ST system. Photovoltaic generation can meet households' whole domestic electricity demand. Solar energy facilities are essential for nearly zero energy residential buildings.